Cyclical dumping and US antidumping protection: 1980 - 2001 - Meredith Crowley (Federal Reserve Bank of Chicago, 2009)
This paper estimates the impact of economic conditions in foreign industries on the filing of antidumping petitions by US industries and the US government's decision in preliminary and final antidumping investigations. Exploiting cross-country variation in economic shocks in manufacturing, I estimate a joint model of filing decisions by the US industry and antidumping decisions by the US government. I find strong evidence that economic weakness in a foreign industry is associated with an increase in the probability of antidumping protection. After controlling for other political and economic factors that likely drive industry filing and government decisions including US GDP growth, I find that a one standard deviation fall in the growth of employment (consumption) in a foreign economy's manufacturing industry doubles (triples) the joint probability that the US industry will file an antidumping petition and the US government will impose a preliminary (temporary) antidumping measure. The effect of weakness in a foreign economy is even larger for final antidumping measures. A one standard deviation fall in foreign employment (consumption) growth increases the joint probability that a petition will be filed and a final (long-lasting) antidumping measure will be imposed by a factor of five (seven). In finding that US trade policy is applied counter-cyclically to foreign economic fluctuations, the paper suggests that trade policy may reduce the extent of business cycle transmission across countries.
Keywords: F12; F13; 330; dumping; anti-dumping; counter-cyclical policy; Dumping; Antidumping; Konjunktur; Interessenpolitik; Theorie; USA